2020
DOI: 10.5194/hess-2020-540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rainfall–Runoff Prediction at Multiple Timescales with a Single Long Short-Term Memory Network

Abstract: Abstract. Long Short-Term Memory Networks (LSTMs) have been applied to daily discharge prediction with remarkable success. Many practical scenarios, however, require predictions at more granular timescales. For instance, accurate prediction of short but extreme flood peaks can make a life-saving difference, yet such peaks may escape the coarse temporal resolution of daily predictions. Naively training an LSTM on hourly data, however, entails very long input sequences that make learning hard and computationally… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…The hypothesis tested in this work was that data-driven streamflow models are likely to become unreliable in extreme or outof-sample events. This is an important hypothesis to test because it is a common concern among physical scientists and among users of model-based information products (e.g., Todini, 2007), however prior work (e.g., Kratzert et al, 2019b;Gauch et al, 2021) demonstrated that data-based rainfall-runoff models were more reliable than other types of physically-based models, even in extrapolation to ungauged basins (Kratzert et al, 2019a). Our results indicate that this hypothesis is incorrect -the data-driven models (both the pure ML model and the physics-informed ML model) were better than benchmark models at predicting peak flows in almost all conditions, including extreme events and including when extreme events were not included in the training data set.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis tested in this work was that data-driven streamflow models are likely to become unreliable in extreme or outof-sample events. This is an important hypothesis to test because it is a common concern among physical scientists and among users of model-based information products (e.g., Todini, 2007), however prior work (e.g., Kratzert et al, 2019b;Gauch et al, 2021) demonstrated that data-based rainfall-runoff models were more reliable than other types of physically-based models, even in extrapolation to ungauged basins (Kratzert et al, 2019a). Our results indicate that this hypothesis is incorrect -the data-driven models (both the pure ML model and the physics-informed ML model) were better than benchmark models at predicting peak flows in almost all conditions, including extreme events and including when extreme events were not included in the training data set.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We used the same set of performance metrics that were used in previous CAMELS studies (Kratzert et al, 2019b(Kratzert et al, , a, 2021Gauch et al, 2021;Klotz et al, 2021). A full list of these metrics is given in Table 1.…”
Section: Performance Metrics and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All code to reproduce our models and analyses is available at https://doi.org/10.5281/zenodo.4687991 (Gauch, 2021). The trained models and their predictions are available at https://doi.org/10.5281/zenodo.4071885 (Gauch et al, 2020a). Hourly NLDAS forcings and observed streamflow are available at https://doi.org/10.5281/zenodo.4072700 (Gauch et al, 2020b).…”
Section: B3 Multi-timescale Input Single-timescale Outputmentioning
confidence: 99%
“…The trained models and their predictions are available at https://doi.org/10.5281/zenodo.4071885 (Gauch et al, 2020a). Hourly NLDAS forcings and observed streamflow are available at https://doi.org/10.5281/zenodo.4072700 (Gauch et al, 2020b). The CAMELS static attributes are accessible at https://doi.org/10.5065/D6G73C3Q (Addor et al, 2017b).…”
Section: B3 Multi-timescale Input Single-timescale Outputmentioning
confidence: 99%